Synthesis of Enantioenriched Tetra-ortho-3,3′-substituted Biaryls by Small-Molecule-Catalyzed Noncanonical Polyketide Cyclizations - Witzig, Reto M.; Sparr, Christof (Synlett, 2020)
The arene-forming aldol condensation is a fundamental reaction in the biosynthesis of aromatic polyketides. Precisely controlled by the polyketide synthases, the highly reactive poly-β-carbonyl substrates are diverged into numerous aromatic natural products by selective cyclization reactions; a fascinating biosynthetic strategy that sparked our interest to investigate atroposelective aldol condensations. In this Account, we contextualize and highlight the ability of small-molecule catalysts to selectively convert noncanonical hexacarbonyl substrates in a double arene-forming aldol condensation resulting in the atroposelective synthesis of tetra-ortho-3,3′-substituted biaryls. The hexacarbonyl substrates were obtained by a fourfold ozonolysis enabling a late-stage introduction of all carbonyl functions in one step. Secondary amine catalysts capable of forming an extended hydrogen-bonding network triggered the noncanonical polyketide cyclization in order to form valuable biaryls in high yields and with stereocontrol of up to 98:2 er.1 Biosynthesis of Aromatic Polyketides2 Rotationally Restricted Aromatic Polyketides3 3,3′-Substituted Binaphthalenes in Catalysis4 Stereoselective Synthesis of Atropisomers5 Synthesis of Enantioenriched Tetra-ortho-3,3′-Substituted Biaryls by the Atroposelective Arene-Forming Aldol Condensation6 Conclusion
Keywords: aldol condensation; atropisomerism; ligand design; polyketides; stereoselective catalysis